Implementation of JemagoWeb for Web File Protection Against Online Gambling Cyber Attacks: Implementasi JemagoWeb untuk Perlindungan File Web dari Serangan Siber Judi Online - Febryan Hari Purwanto Hari; Firmansyah Alfarisi (STMIK PONTIANAK, 2026)
Cyberattacks targeting web files through unauthorized uploads, edits, and deletions are common, especially on websites targeted by online gambling hackers. This study develops and implements JemagoWeb, a web file protection system based on a cron job that performs automatic detection every minute of suspicious file changes. The system proactively prevents illegal file uploads via an auto-delete mechanism and restores missing or modified files by comparing current files to original backups. The name JemagoWeb is derived from the Rejang word “jemago,” meaning “to guard,” reflecting the system’s role as a guardian of web file security and integrity. Testing conducted in a shared hosting environment vulnerable to malicious file attacks demonstrated JemagoWeb’s effectiveness in maintaining real-time file integrity and availability. By employing an automated, time-based approach, JemagoWeb offers a practical solution to mitigate online gambling cyberattacks, enhancing website security without compromising hosting performance.